1972
DOI: 10.1021/je60055a029
|View full text |Cite
|
Sign up to set email alerts
|

Excess thermodynamic properties of ethylenediamine-ethylene glycol solutions at 25.deg.

Abstract: The excess Gibbs free energies, enthalpies, entropies, and volumes are reported for mixtures of ethylene diamine-ethylene glycol at 25°C. The refractive indices of these liquid mixtures are also reported for 25°C.The excess thermodynamic properties have been reported for water-diethylamine solutions at 49.1°C, and ethyl alcoholdiethylamine solutions at 50°C. In both mixtures the excess enthalpies are large and negative over the entire composition range. The same is true for the TsE values. However, the Gibbs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 3 publications
(6 reference statements)
3
6
0
Order By: Relevance
“…The experimental the refractive indices (n D ) were in good agreement with literature values [26,[56][57][58] at 298.15 K. The variation of excess refractive indices (R E m ) with the mole fraction of DO (x 1 ) at 298.15 K also reveals that the same order of molecular interactions for the studied blends as discussed above. …”
Section: Molar Refractionssupporting
confidence: 89%
See 1 more Smart Citation
“…The experimental the refractive indices (n D ) were in good agreement with literature values [26,[56][57][58] at 298.15 K. The variation of excess refractive indices (R E m ) with the mole fraction of DO (x 1 ) at 298.15 K also reveals that the same order of molecular interactions for the studied blends as discussed above. …”
Section: Molar Refractionssupporting
confidence: 89%
“…Table 1 contains provenance and purity of the chemicals used in this work. Purity of the solvents was ascertained by GLC and also by comparing their densities and viscosities at the experimental temperatures with the literature data [20][21][22][23][24][25][26][27][28][29][30][31], whenever available, as shown in Table S1 of the Supporting information.…”
Section: Chemicalsmentioning
confidence: 99%
“…Alternatively, entropy has been emphasized in the studies of glass transition phenomenology, and an excess T g is explained by a decrease of entropy. Among isomers of the same intermolecular interaction nature, the difference in T g is found to be dominated by entropy . Experimental observations show that the pronounced positive deviation of T g in mixtures is also generally accompanied by a negative mixing entropy, ,, suggesting the association of unlike components. , A recent molecular dynamic simulation study also found that the positive deviation of viscosity from the ideal mixing rule is associated with a negative deviation of configurational entropy . By contrast, a negative excess T g behavior like that shown for MMT−MOT solutions (Figure ) has been reported only rarely. ,, According to Lesikar’s studies, entropy-dominated mixing explains the negative deviation in T g .…”
Section: Discussionmentioning
confidence: 99%
“…(en)H + + (en-H) − , takes place to a low extent [19]. Investigations of the conformational energy and the structural stability of ethylenediamine by ab initio methods show that the two most stable conformations are stabilized by intramolecular hydrogen bonding (N-H · · · N) with stabilization energies up to 20 kcal mol −1 [20,21].…”
Section: Introductionmentioning
confidence: 99%